ARM Cortex-M3 Processor and MBED NXP LPC1768 - Elahi, Ata; Arjeski, Trevor (ARM Assembly Language with Hardware Experiments, 2015)
ARM offers variety of the core processor base on their applications and they are: Cortex A series: Cortex A series is a High performance processor for open operating system, the Cortex-A50 is a 64 bit process, application of Cortex-A series are Smart phones, Netbook, Digital TV, and eBook readers
Keywords: dept.csc